Socioecological factors influencing sugar-sweetened beverage consumption among adolescents in South Korea: a cross-sectional study - Jin Suk Ra; Sun Hwa Kim (Child Health Nursing Research)
Purpose This study explored the intrapersonal, interpersonal, and school factors, following the socioecological model, associated with sugar-sweetened beverage (SSB) consumption in Korean high-school students. Methods A total of 231 students from first to third grade, aged 15–18 years, participated in this cross-sectional study. Multiple linear regression analysis was conducted to identify the factors. Results Among the intrapersonal factors, fast-food consumption (β=0.13, t=1.97, p=.050) and habit strength of SSB consumption were positively associated (β=0.35, t=4.30, p<.001), and sleep duration was negatively associated with SSB consumption (β=–0.14, t=–2.02, p=.045). Among interpersonal factors, perceived SSB consumption by peers was positively associated (β=0.30, t=4.93, p<.001), and among school factors, vending machines at school (β=0.13, t=2.07, p=.039) and supermarkets and convenience stores near schools were positively associated with SSB consumption (β=0.17, t=2.87, p=.005). Conclusion School nurses should propose policies and interventions that consider the multilevel factors to reduce SSB consumption in adolescents.